2009
DOI: 10.1159/000205385
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the PQRST Intervals and Heart Rate Variability Associated with Rewarming in Two Newborns Undergoing Hypothermia Therapy

Abstract: Background: Little is known about the effects of hypothermia therapy and subsequent rewarming on the PQRST intervals and heart rate variability (HRV) in term newborns with hypoxic-ischemic encephalopathy (HIE). Objectives: This study describes the changes in the PQRST intervals and HRV during rewarming to normal core body temperature of 2 newborns with HIE after hypothermia therapy. Methods: Within 6 h after birth, 2 newborns with HIE were cooled to a core body temperature of 33.5°C for 72 h using a cooling bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
2
23
0
2
Order By: Relevance
“…Our findings of increased HRV at lower temperatures are consistent with prior animal (25) and human studies(28, 29, 33) evaluating HRV in the temperature range of moderate therapeutic hypothermia. The temperature-dependency of HRV may be explained via several possible mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings of increased HRV at lower temperatures are consistent with prior animal (25) and human studies(28, 29, 33) evaluating HRV in the temperature range of moderate therapeutic hypothermia. The temperature-dependency of HRV may be explained via several possible mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…(28) Only one small study involving 2 newborns undergoing TH for HIE likewise reported a negative association between LF Power and temperature. (33) These investigators also found a negative association between HF Power and temperature as well as a positive association between LF/HF ratio and temperature. We did not evaluate LF/HF ratio as recent reports have questioned whether this measure accurately reflects the sympatho-vagal balance as originally proposed.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Frequency domain indices were adapted to temporal and spectral features of neonatal cardiovascular signals [17]: very low frequency power (0.005 - 0.04 Hz), low frequency power (0.04 - 0.25 Hz) and high frequency power (0.25 - 0.85 Hz).…”
Section: Methodsmentioning
confidence: 99%